Research metrics of Australian eating disorders researchers - Felicia Reed; Maddy Lyon; Anita Raspovic; Peta Marks; Sarah Maguire; Leah Brennan; Claire J. Foldi (Journal of Eating Disorders)
Abstract Building the research capacity and capability of Australia’s eating disorder (ED) research workforce has been identified as a key strategy to respond to the increasing prevalence of EDs. However, there is currently a limited understanding of the research strengths and scope of this workforce and this is a barrier to capacity building efforts and to evaluating the impacts of these efforts. This study sought to understand and summarise the current research metrics of the top 50 research experts in Australia identified through Expertscape. Publicly available publication, citation and funded research grants metrics, were extracted from Expertscape, Scopus, SciVal, Dimensions.ai and researcher profiles and summarised. The results indicate that Australian Feeding and Eating Disorder (FED) researchers are competitive internationally, and are spread across professional disciplines with the highest representation from psychology. Expertscape researcher rank was associated with higher numbers of publications in feeding and eating disorders overall, but not to total outputs, field-weighted citation impact (FWCI), or number of publications in top percentile journals. Publications were heavily focused on Anorexia Nervosa. Public grants awarded to the identified ED researchers in Australia over the past 10 years were largely National Health and Medical Research Council (NHMRC) project grant schemes, targeting innovative and creative research across any area of health and medical research. Cumulative dollars awarded over the 10-year period up to 2023 were approximately $23.9 million AUD, roughly 6 times less than that awarded to Schizophrenia research. These results summarise the current state of Australian FED research, comprised of a productive high performing research workforce limited by inadequate research funding.